The Use of Intersectional Analysis in Assessing Women's Leadership Progress in the Health Workforce in LMICs: A Review - Zahra Zeinali; Kui Muraya; Sassy Molyneux; Rosemary Morgan (Kerman University of Medical Sciences, 2022)
BackgroundHuman resources are at the heart of health systems, playing a central role in their functionality globally. It is estimated that up to 70% of the health workforce are women, however, this pattern is not reflected in the leadership of health systems where women are under-represented. MethodsThis systematized review explored the existing literature around women's progress towards leadership in the health sector in low- and middle-income countries (LMICs) which has used intersectional analysis. ResultsWhile there are studies that have looked at the inequities and barriers women face in progressing towards leadership positions in health systems within LMICs, none explicitly used an intersectionality framework in their approach. These studies did nevertheless show recurring barriers to health systems leadership created at the intersection of gender and social identities such as professional cadre, race/ethnicity, financial status, and culture. These barriers limit women's access to resources that improve career development, including mentorship and sponsorship opportunities, reduce value, recognition and respect at work for women, and increase the likelihood of women to take on dual burdens of professional work and childcare and domestic work, and, create biased views about effectiveness of men and women's leadership styles. An intersectional lens helps to better understand how gender intersects with other social identities which results in upholding these persisting barriers to career progression and leadership. ConclusionAs efforts to reduce gender inequity in health systems are gaining momentum, it is important to look beyond gender and take into account other intersecting social identities that create unique positionalities of privilege and/or disadvantage. This approach should be adopted across a diverse range of health systems programs and policies in an effort to strengthen gender equity in health and specifically human resources for health (HRH), and improve health system governance, functioning and outcomes.